Consultoria e assistência técnica no agronegócio: um estudo de caso no estado do Tocantins - Nunes, Priscilla Oliveira (Universidade Federal do Tocantins, 2021)
This research aimed to analyze the impact generated for agricultural businesses by the services offered by a rural consultancy and technical assistance company. Innovations in business management, the process of modernization of agribusiness in Brazil and Tocantins were studied, as well as the work of consultancy and rural technical assistance companies and the granting of rural credit. With clipping for a consultancy company in the city of Palmas-TO and 37 client companies of the consultancy company. The investigation had a qualitative approach as methodology, configuring itself in bibliographic, field and descriptive research. The research revealed the evolution of agribusiness companies, which need to adapt to survive in the market, and one of the ways to keep these companies competitive is the hiring of consultancy and rural technical assistance companies. As a result, it was found that the main impact generated to agricultural companies is related to their financial gains, which increases their income after going through a Consulting service, since the most sought after and offered service is the investment project. However, it is expected to contribute to the improvement of management in rural businesses, noting the importance of consultancies in this process.